2018
DOI: 10.3837/tiis.2018.04.024
|View full text |Cite
|
Sign up to set email alerts
|

A Coordinated Ciphertext Policy Attribute-based PHR Access Control with User Accountability

Abstract: The personal health record (PHR) system is a promising application that provides precise information and customized services for health care. To flexibly protect sensitive data, attribute-based encryption has been widely applied for PHR access control. However, escrow, exposure and abuse of private keys still hinder its practical application in the PHR system. In this paper, we propose a coordinated ciphertext policy attribute-based access control with user accountability (CCP-ABAC-UA) for the PHR system. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Tembhare et al [14] introduced a system called MediTrust that combined RBAC with ABE systems and utilized a contextualized repository to enhance efficiency of PHR domain. Lin et al [15] suggested a coordinated CPAB-PHR access control with user accountability (CCP-ABAC-UA). This scheme provided synchronous generation and distributed storage of private keys, which effectively prevented the exposure and escrow of private keys.…”
Section: The Authors Stated the New Technique As Combined Attribute B...mentioning
confidence: 99%
“…Tembhare et al [14] introduced a system called MediTrust that combined RBAC with ABE systems and utilized a contextualized repository to enhance efficiency of PHR domain. Lin et al [15] suggested a coordinated CPAB-PHR access control with user accountability (CCP-ABAC-UA). This scheme provided synchronous generation and distributed storage of private keys, which effectively prevented the exposure and escrow of private keys.…”
Section: The Authors Stated the New Technique As Combined Attribute B...mentioning
confidence: 99%